Metode Rapid Application Development Dalam Pengembangan Sistem Informasi Perpustakaan Berbasis Web - Hidayatulloh, Syarif; Patyani, Enda (Computer Science (CO-SCIENCE), 2024)
The information system is crucial for business processes in all fields, including education. A library at SMK Negeri 1 Jawai, Sambas Regency, currently manages its data, borrowing, and book return processes manually, using physical records and writing tools. With such management, the library faces various challenges. Common issues include students having difficulty tracking borrowed books, problems with lost returns, and discrepancies in the number of loans and returns. Therefore, this research aims to improve business processes at SMK Negeri 1 Jawai's library by developing a web-based information system tailored to its needs. Rapid Application Development was chosen as the development method for this library information system due to its ability to quickly produce a high-quality system. The method involves stages such as requirement planning, system design, and implementation. RAD is capable of creating a website that provides objective information. The resulting Information System from this research was tested using Blackbox Testing, which confirmed that all features and processing flows functioned correctly.